2017
DOI: 10.18632/oncotarget.20059
|View full text |Cite|
|
Sign up to set email alerts
|

Berberine and cinnamaldehyde together prevent lung carcinogenesis

Abstract: Starving tumor cells by restricting nutrient sources is a promising strategy for combating cancer. Because both berberine and cinnamaldehyde can activate AMP-activated protein kinase (AMPK, a sensor of cellular energy status), we investigated whether the combination of berberine and cinnamaldehyde could synergistically prevent lung carcinogenesis through tumor cell starvation. Urethane treatment induced lung carcinogenesis in mice, downregulated AMPK and mammalian target of rapamycin (mTOR) while upregulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Lung function was analyzed by maximal mid-expiratory flow using the animal respiratory metabolic measurement system (Sable Systems International, United States). Lung permeability was assessed with the Evans blue dye extra-barrier technique and the wet/dry ratio of lungs according to our previous method (Meng et al, 2017). Lung injury was evaluated by pathohistological examination.…”
Section: Methodsmentioning
confidence: 99%
“…Lung function was analyzed by maximal mid-expiratory flow using the animal respiratory metabolic measurement system (Sable Systems International, United States). Lung permeability was assessed with the Evans blue dye extra-barrier technique and the wet/dry ratio of lungs according to our previous method (Meng et al, 2017). Lung injury was evaluated by pathohistological examination.…”
Section: Methodsmentioning
confidence: 99%
“…With the indepth study of other functions of berberine, it has been found that berberine also has pharmacological effects such as lowering blood lipid, lowering blood sugar, antiarrhythmia, expanding coronary vessels and antihypertension [25]. In recent years, a large number of studies have shown that berberine has anti-tumor effect, and can participate in the anti-tumor process of liver cancer [28], lung cancer [29], colon cancer [30], bladder cancer [31], and other malignant tumors. The antitumor mechanism of berberine is still under constant study.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1E, compared with the vector group, CA could also dose-dependently inhibit the growth of the tumors (detailed data provided in Figure S2). 24,48, or 72 h, and the cell viability was assayed. (C) A375 cells were treated with 0, 0.5, 1, 2, or 4 µM CA for 12 days, and Giemsa staining was used to conduct colony-formation assays; the histogram shows the number of colonies (n = 3), scale bar: 10 µm.…”
Section: Ca Inhibited A375 Cell Growth In Vitro and In Vivomentioning
confidence: 99%
“…[19][20][21][22]. In addition, CA can treat various types of cancer, including leukemia, hepatocellular carcinoma, and colon, breast, prostate, and oral cancers [23][24][25][26]. Only a few studies have reported that CA can inhibit the growth of melanoma cells and tumor growth [27], but the mechanism and target protein are not clearly explained.…”
Section: Introductionmentioning
confidence: 99%